(4j+2(j+1.5))/6=16

Simple and best practice solution for (4j+2(j+1.5))/6=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4j+2(j+1.5))/6=16 equation:



(4j+2(j+1.5))/6=16
We move all terms to the left:
(4j+2(j+1.5))/6-(16)=0
We multiply all the terms by the denominator
(4j+2(j+1.5))-16*6=0
We calculate terms in parentheses: +(4j+2(j+1.5)), so:
4j+2(j+1.5)
We multiply parentheses
4j+2j+3
We add all the numbers together, and all the variables
6j+3
Back to the equation:
+(6j+3)
We add all the numbers together, and all the variables
(6j+3)-96=0
We get rid of parentheses
6j+3-96=0
We add all the numbers together, and all the variables
6j-93=0
We move all terms containing j to the left, all other terms to the right
6j=93
j=93/6
j=15+1/2

See similar equations:

| -7d+6=-6d | | -5(a-2)=-25 | | 32.8+h-38.17=20 | | -8-8(1+4a)=-272 | | -3-6s=8+5s | | 4a+1.3=5a-6.5 | | -10+5c-8=2c+9 | | -4+8p+88=10+7p | | -5z=-4-6z | | -180=15b | | -9-10j=-7-9j | | 5n+5=-5-8n-2 | | x+x+x=600 | | 1-6k=10-9k | | 9f-6=8+2f | | 5-4(4x+7)=89 | | -8q+1=10-9q | | 8n=-4+9n | | 4.2x=4x+2 | | -r+3=-2r | | 1=-7+n/4 | | -9s+4=-10s | | W.0.05w+925=0.03w+1250 | | 3k^2+2=41 | | x6=24. | | b/3-6=30 | | 4y-3/7=3 | | -9+6z=6-9z | | 27y/28-7=1-4y/7 | | 5a-80=70 | | 6-9p=-5p-9-9 | | 3k+2=41 |

Equations solver categories